Assessing the performance of DG in distribution network - Siti Rafidah, Abdul Rahim; Ismail, Musirin, Dr.; Mohd Herwan, Sulaiman, Dr.; Muhd Hatta, Hussain; Azralmukmin, Azmi (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/